Bốn nhóm yếu tố dịch vụ ngân hàng có tác động bất đối xứng và đa chiều đến sự hài lòng và bất mãn của khách hàng - Vo Thi Ngoc , Thuy (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2017)
This study examines the impact of various service attributes on (dis)satisfaction of customers with traditional transactional services at public banks. The study approaches customer satisfaction and dissatisfaction as two asymmetric concepts. The qualitative study finds 45 service attributes of transactional services. An application of the Kano method subsequently leads to the categorization of these service attributes into four groups that have the different logics to impact on customers dis(satisfaction). Among them three groups do not have the linear effects. Accordingly, the findings enable public banks’ managers to define the service attributes that truly have important effects on customers’ satisfaction and those rendering customers dissatisfaction to accordingly optimize the input costs of each of the service attributes which still please customers.
Keywords: Satisfaction; Disatisfaction; Customers; Banking services; Asymmetrical effects; Kano’s model